Regular walking improves plasma protein concentrations that promote blood hyperviscosity in women 65-74 yr with type 2 diabetes - Simmonds, M.; Sabapathy, S.; Serre, K.; Haseler, Luke; Gass, G.; Marshall-Gradisnik, S.; Minahan, C. (2016)
© 2016 - IOS Press and the authors. All rights reserved. BACKGROUND: The purpose of the present study was to investigate the effects of regular treadmill walking on plasma factors that increase low-shear blood viscosity and red blood cell aggregation in older women with type 2 diabetes. METHODS: Eighteen women with type 2 diabetes (age: 69±3 yr; body mass index: 30.5±5.0 kg·m -2 ) performed 12-wk of 120 min·wk -1 of supervised treadmill walking at an intensity equivalent to the gas-exchange threshold. Peak exercise values, anthropometry and blood indices of diabetic status, markers of inflammation, and plasma fibrinogen were analysed during a 6-wk pre-training 'control' period, and then after 6 and 12-wk of regular walking. RESULTS: Regular walking significantly increased peak oxygen uptake (p = 0.01). Body mass, waist to hip ratio, and glycaemic control did not change. Systolic and diastolic blood pressures decreased by 8.5 (p < 0.01) and 7.2 (p < 0.01) respectively, cholesterol to high-density lipoprotein (HDL) ratio decreased by 9.6 (p = 0.01), and HDL concentration significantly increased (p = 0.01). While 12 wk of regular walking did not significantly alter plasma concentrations of interleukin-6 (IL-6), tumour necrosis factor-a, or C-reactive protein, plasma fibrinogen concentration decreased by 6.9 (p < 0.01) and plasma interleukin-10 (IL-10) concentration increased from 1.15±0.32 to 1.62±0.22 mmol·L -1 (p < 0.04). CONCLUSIONS: Improved plasma inflammatory profile and decreased plasma fibrinogen concentration is induced by regular walking, independent of glycaemic control. These factors may mediate the improved haemorheology associated with exercise training in metabolic disorders.